Sports Facility Management Model for Rajabhat Universities - Charnnarong, Palakorn; Sawangmek, Taweesak; Roonprapunta, Kajornsak; Tiaotrakul, Arphat (Dhammathas Academic Journal, 2022)
This research’s objectives were to 1) study the condition and management guidelines of sports facilities. 2) construct and examine a sports facilities management model of Rajabhat University and 3) assess the feasibility of implementing a sports facilities management model of Rajabhat University. This research is research and development. The procedures for conducting this research were three-fold, 1. study the condition and management of sports facilities of Rajabhat University. The sample group consisted of 400 people by stratified random sampling by comparing the proportions of the samples from the population of each region and study guidelines on the management of sports facilities from 3 experts and study good practice in sports facilities management within 2 institutions. 2. Create and validate the model by taking the information from Step 1 to draft a sports facility management model and verify the suitability of the model with a group discussion. 3. Assess the feasibility of the implementation using the sample group consisting of executives and sports practitioners in 38 Rajabhat universities, 2 people each. The statistics used to analyze the data are Mean and Standard Deviation. The findings were as follows: 1. Conditions and guidelines for the management of sports facilities of Rajabhat University at a good level. 2. The management model built consists of 3 components as follows: 1) The inputs consist of personnel, budget, materials, equipment, and facilities. management and marketing ingredients 2) management processes consisting of planning, organization, leadership, and control 3) productivity, students, personnel, and people participating in exercise and sports for health. 3. Assessment of the feasibility of applying the developed sports facilities management model has a high level of feasibility for adoption.